Relationship between illness perception, fear of progression and quality of life in interstitial lung disease patients: A cross‐sectional study - Liu, Qing‐wei; Qin, Tong; Hu, Bo; Zhao, Ya‐ling; Zhu, Xiu‐li (Journal of clinical nursing, 2021)
Aims and objectives This study aimed to investigate whether fear of progression mediates the association between illness perception and quality of life among interstitial lung disease patients. Background So far, the physiological treatment of interstitial lung disease is limited. In addition to immunosuppressants such as glucocorticoids, two anti‐fibrosis drugs (pirfenidone and nintedanib) have shown moderately beneficial effects on slowing the progression of interstitial lung disease fibrosis. However, none of these drugs has shown reliable or strong beneficial effects on improving quality of life. Psychological care and mental health support strategies focusing on improving patients' quality of life are particularly important. Design A cross‐sectional study. Methods A convenience sample of patients suffering from interstitial lung disease were enrolled from August to December 2019. Data including sociodemographic and clinical characteristics, illness perception, fear of progression and quality of life were collected. The descriptive analysis and Pearson correlations were analysed by SPSS 26.0 (IBM Corp.). PROCESS v3.4 (by Andrew F. Hayes) macro was applied to analyse the mediating effects. We used the STROBE checklist to report the results. Results Both illness perception and fear of progression were correlated with quality of life. Fear of progression mediated the association between illness perception and quality of life. The indirect effect was 0.121, and the proportion of intermediary effect in the main effect was 26.36%. Conclusion Interstitial lung disease patients experience relatively poor quality of life and fear of progression exerts a mediating role between illness perception and quality of life. Relevance to clinical practice This study alerts medical staff to pay attention to negative illness perception and excessive fear, which is helpful to formulate effective interventions to manage interstitial lung disease patients' quality of life.